MicroRNA-200c modulates epithelial-to-mesenchymal transition (EMT) in human colorectal cancer metastasis. Issue 9 (26th June 2012) - Hur, Keun; Toiyama, Yuji; Takahashi, Masanobu; Balaguer, Francesc; Nagasaka, Takeshi; Koike, Junichi; Hemmi, Hiromichi; Koi, Minoru; Boland, C Richard; Goel, Ajay
Abstract : Objective: Distant metastasis is the major cause of cancer-related death in patients with colorectal cancer (CRC). Although the microRNA-200 (miR-200) family is a crucial inhibitor of epithelial-to-mesenchymal transition (EMT) in human cancer, the role of miR-200 members in the pathogenesis of metastatic CRC has not been investigated. Design: Fifty-four pairs of primary CRC and corresponding matched liver metastasis tissue specimens were analysed for expression and methylation status of the miR-200 family members. Functional analysis of miR-200c overexpression was investigated in CRC cell lines, and cells were analysed for proliferation, invasion and migration. Expression of several miR-200c target genes ( ZEB1, ETS1 and FLT1 ) and EMT markers (E-cadherin and vimentin) in CRC cell lines and tissue specimens was validated. Results: Liver metastasis tissues showed higher expression of miR-200c (primary CRC=1.31 vs. liver metastasis=1.59; p=0.0014) and miR-141 (primary CRC=0.14 vs. liver metastasis=0.17; p=0.0234) than did primary CRCs, which was significantly associated with hypomethylation of the promoter region of these miRNAs (primary CRC=61.2% vs. liver metastasis=46.7%; p<0.0001). The invasive front in primary CRC tissues revealed low miR-200c expression by in situ hybridization analysis. Transfection of miR-200c precursors resulted in enhanced cell proliferation but reduced invasion and migration behaviours in CRC cell lines. Overexpression of miR-200c in CRC cell lines caused reduced expression of putative gene targets, and resulted in increased E-cadherin and reduced vimentin expression. The associations between miR-200c, target genes and EMT markers were validated in primary CRCs and matching liver metastasis tissues. Conclusions: miR-200c plays an important role in mediating EMT and metastatic behaviour in the colon. Its expression is epigenetically regulated, and miR-200c may serve as a potential diagnostic marker and therapeutic target for patients with CRC.